Pengaruh Beauty Influencer, Customer Review, dan Customer Rating terhadap Minat Beli Produk Skincare Garnier Pada Konsumen Belia Cosmetic Di Shopee - Nidia Prastika; Eko Agus Alfianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Before there is an interest in buying a product, consumers will first search for product information in various ways. One of them is by looking at review information on several social media, blogs, websites, and favorite influencers. This study aims to determine the effect of Beauty Influencers, Customer Reviews, and Customer Ratings on Interest in Buying Garnier skincare products. The population in this study are Belia Cosmetic consumers at Shopee. This study uses a quantitative approach. The data collection technique was carried out by distributing questionnaires to 100 respondents using a non-probability sampling method through a purposive sampling technique. The results of the study show that beauty influencers have no positive and significant effect on purchase intention. The results of the study show that customer reviews have a positive and significant effect on purchase intention. The results of the study show that customer ratings have a positive and significant effect on purchase intention. The results show that the variables beauty influencer, customer review, and customer rating have a positive and significant effect on the intention to buy Garnier skincare products.